2019
DOI: 10.1101/679308
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Type I-F CRISPR-Cas resistance against virulent phage infection triggers abortive infection and provides population-level immunity

Abstract: Type I CRISPR-Cas systems are the most abundant and widespread adaptive immune systems of bacteria and can greatly enhance bacterial survival in the face of temperate phage infection. However, it is less clear how these systems protect against virulent phages. Here we experimentally show that type I CRISPR immunity of Pectobacterium atrosepticum leads to rapid suppression of two unrelated virulent phages, ΦTE and ΦM1. However, unlike the case where bacteria are infected with … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The biological role of NucC in type III CRISPR systems remains unclear. It is possible that incorporation of NucC into a CRISPR system converts this system from a specific defensive pathway into an abortive infection system; indeed, recent reports have shown that certain type IF and type VI CRISPR systems can act via abortive infection (Meeske et al, 2019;Watson et al, 2019). Alternatively, NucC's cleavage activity may be spatially or temporally restrained in these systems to limit its potential to destroy the host genome.…”
Section: Discussionmentioning
confidence: 99%
“…The biological role of NucC in type III CRISPR systems remains unclear. It is possible that incorporation of NucC into a CRISPR system converts this system from a specific defensive pathway into an abortive infection system; indeed, recent reports have shown that certain type IF and type VI CRISPR systems can act via abortive infection (Meeske et al, 2019;Watson et al, 2019). Alternatively, NucC's cleavage activity may be spatially or temporally restrained in these systems to limit its potential to destroy the host genome.…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, most middle spacers would not be identified as "locally adapted" simply because they succeeded in eliminating their targets. Although CRISPR immunity can effectively prevent MGE proliferation in culture (80,81), it is less likely that complete elimination of MGE occurs in complex, spatially extended microbial communities (26,82) (and the human gut virome appears indeed highly stable over time (83)). More generally, this scenario does not account for the possibility that the same MGE is targeted by multiple spacers located at different positions in different arrays, which would effectively decouple within-array spacer positions and population-level MGE abundances.…”
Section: Selection Promotes Long-term Immunity Against Endemic Mgementioning
confidence: 99%
“…Hosts with abortive infection allow phages to enter and kill them without producing a noticeable phage progeny (13). An example of the Abi defense is provided by certain types of CRISPR defense (2729), where phages kill most of infected hosts but have zero or small burst size. In contrast to Abi- or CRISPR-protected bacteria, partially resistant strains may arise due to a mutation in the receptor protein which reduces both the growth rate (30) and the phage adsorption but has little effect on the burst size.…”
Section: Discussionmentioning
confidence: 99%